The Right to Privacy between Constitutional and Penal Legislations in Palestine - Jihad Alkiswani; Abdelmalik Alrimawi (International Journal of Law Research and Studies, 2025)
The right to privacy has emerged in the current century as one of the most significant individual rights affected by technological development, particularly through cybercrimes and advances in artificial intelligence. This evolution has been accompanied by the adoption and use of such means, especially in criminal prosecution. This study aims to examine the right to privacy within the framework of constitutional and penal legislations in Palestine, with the objective of identifying the extent to which constitutional provisions and substantive and procedural penal legislations protect this fundamental right in light of contemporary challenges such as technological advancement, cybercrimes. Moreover, artificial intelligence. The study seeks to assess the compatibility of penal legislations with constitutional guarantees through a comparative presentation of international experiences to identify the strengths and weaknesses of national legislations and propose methods for their development. To this end, the inductive-analytical method was employed, enabling the researchers to analyze legal rules, examine their scope of application. Moreover, derive generalizations that highlighted the weak constitutional protection of the right to privacy. Moreover, the study observed violations of this right in procedural aspects of criminal law and noted the inadequacy of its substantive penal protection due to limited capabilities in addressing violations of correspondence confidentiality, phone tapping, infringement of image rights. Moreover, the repercussions of artificial intelligence. The study recommends strengthening legislative and judicial protection of privacy, while emphasizing the need to strike a balance between this right and the requirements of societal security in the digital age.